Passenger Queue Simulation Analysis and Optimization at The Check-in Counter of Yogyakarta International Airport - Putra, Ananda Adhitya; Rahmawati, Fajar Khanif; Mulyani, Sri; Kusumaningrum, Maria Asumpta Deny; Gunawan, Gunawan; Medianto, Rully (Compiler, 2024)
Air transportation has a role in providing services to deliver people and goods in a relatively shorter time. Queues will increase due to the relatively low quality and quantity of service. This can happen at the Yogyakarta International Airport check-in counter. This research uses a comparison method between the queuing system and arena software. The queuing system used is a single channel-single phase.  The airlines that will be studied are Lion Air and Super Air Jet. The samples used respectively were 65 passengers and 61 passengers from Lion Air and Super Air Jet airlines. Data collection was carried out during peak hours. With this passenger movement simulation model, it is possible to determine the length of queue experienced by passengers at each check-in counter, the time to be served, and the check-in counter staff that must be provided. The length of time queuing for passengers for each airline is that for Lion Air the length of time queuing at the check-in counter is 18,6 minutes with an additional 1 officer from before and for Super Air Jet it is 28,5 minutes with an additional 1 officer from the previous check-in counter.